Effects of agricultural mechanization on economies of scope in crop production in Nigeria - Takeshima, Hiroyuki; Hatzenbuehler, Patrick L.; Edeh, Hyacinth O. (International Food Policy Research Institute, 2018)
Agricultural mechanization has often been characterized by scale-effects and increased specialization. Such characterizations, however, fail to explain how mechanization may grow in Africa where production environments are more heterogeneous and diversification of production may help in mitigating risks from increasingly uncertain climatic conditions. Using panel data from farm households and crop-specific production costs in Nigeria, we estimate how the adoption of animal traction or tractors affects the economies of scope (EOS) between rice, non-rice grains, legume/seed crops, and other crops, which are the crop groups that are most widely grown with animal traction or tractors in Nigeria. The results indicate that the adoption of these mechanization technologies is associated with lower EOS between non-rice grains, legume/seed crops, and other crops, but greater EOS between rice and other crops. An increase in EOS for rice is indicated in both primal and dual analytical approaches. Mechanical technologies may raise EOS between crops that are grown in more heterogeneous environments, even though it may lower EOS between crops that are grown in relatively similar environments. To the best of our knowledge, this is the first paper that shows the effects of mechanical technologies on EOS in agriculture in developing countries.